2020
DOI: 10.1002/jcp.29915
|View full text |Cite
|
Sign up to set email alerts
|

Bovine peripheral blood MSCs chemotax towards inflammation and embryo implantation stimuli

Abstract: Mesenchymal stem cells (MSCs) have a great potential in regenerative medicine because of their multipotential and immunoregulatory capacities, while in early pregnancy they could participate in the immunotolerance of the mother towards the embryo. Peripheral blood constitutes an accessible source of MSCs. We successfully isolated peripheral blood MSC (pbMSCs) lines, with or without previous bone marrow mobilization. All pbMSCs lines obtained in both conditions presented classical MSC markers and properties, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 48 publications
(78 reference statements)
4
41
1
Order By: Relevance
“…Recently, our group characterized for the first time endometrial mesenchymal stem cell lines (eMSC) [ 11 ] as well as peripheral blood MSC (pbMSCs) lines [ 12 ]. While eMSC showed a reduced migratory capacity in response to the implantation cytokine IFN-τ [ 11 ], pbMSC showed chemotactic behavior to both inflammation (TNFα, IL1β), embryo implantation stimuli (IFN-τ) or BBT-secretome, suggesting that the embryo secretome plays a role in ensuring the retention of eMSC and the active recruitment of MSCs from bone marrow during early pregnancy to repress the immune response to prevent the embryo rejection by the maternal organism [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group characterized for the first time endometrial mesenchymal stem cell lines (eMSC) [ 11 ] as well as peripheral blood MSC (pbMSCs) lines [ 12 ]. While eMSC showed a reduced migratory capacity in response to the implantation cytokine IFN-τ [ 11 ], pbMSC showed chemotactic behavior to both inflammation (TNFα, IL1β), embryo implantation stimuli (IFN-τ) or BBT-secretome, suggesting that the embryo secretome plays a role in ensuring the retention of eMSC and the active recruitment of MSCs from bone marrow during early pregnancy to repress the immune response to prevent the embryo rejection by the maternal organism [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the BBT-9, thanks to its mesenchymal phenotype, could play an immunomodulatory role via EV signaling, aimed at guaranteeing the survival of the embryo. Our group has also reported the immunomodulatory capacity of eMSC and pbMSC by inhibiting the proliferation of human T lymphocytes [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CCL2 plays a role in the recruitment of immune regulatory cells to implantation sites within the bovine endometrium 47 . Interestingly, Calle et al 48,49 reported that bovine mesenchymal stem cells from peripheral blood and endometrium migrate toward for inflammatory stimuli and/or implantation cytokine (interferon‐tau) to ensure the immunomodulation necessary in the mother for embryo survival. Therefore, inflammatory conditions in the oviduct are expected to contribute to both physiological conditions for pregnancy, such as embryo development, and pathological conditions, such as infertility, and further detailed examination is required.…”
Section: Discussionmentioning
confidence: 99%
“…The mesenteric lymph nodes also express ISG15 (Oliveira et al, 2008) and the traffic of immune cells through that could be a source of IFN-τ stimulus. Additionally, there are in vitro evidence that peripheral blood mesenchymal stem cells (pbMSC) increase their migratory capacity in response to IFN-τ treatment, which could be a chemotaxis stimulus to the uterus (Calle et al, 2021). Immune cells have important roles during pregnancy establishment (Berkowitz et al, 1988;Fair, 2015); however, the functions for each ISG up regulated in PBMC and PMN have not been determined.…”
Section: Autocrine Endocrine and Paracrine Actions Of Interferon-taumentioning
confidence: 99%